PENGARUH BIAYA PRODUKSI, BIAYA OPERASIONAL, DAN VOLUME PENJUALAN TERHADAP LABA BERSIH PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMEN PRIMER YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2020-2022 - Issulistaningtyas Okta An-nisa; Wikan Budi Utami; Indra Lila Kusuma (CV. Denasya Smart Publisher, 2025)
This study aims to examine the effect of production costs, operating costs, also sales volume on net income of primary consumer goods sector companies listed on the Indonesia Stock Exchange for the period 2020-2022. This study uses secondary data in the form of company financial reports obtained from the official website www.idx.co.id. The sampling technique in this study used purposive sampling method. The analysis method used in this research is multiple linear regression with the help of SPSS 23 software. The results showed that production costs, operating costs, and sales volume simultaneously had an influence of 96.3% in determining the amount of the company's net profit. Partially, it shows that production costs and operational costs have a negative and significant effect on the company's net profit. While sales volume has a positive and significant effect on net profit.